POTRET PEMIKIRAN ISLAM DI ERA TRANSISI (SEBUAH FENOMENA MENURUNNYA GAIRAH PEMIKIRAN ISLAM DI INDONESIA) - Faisal Attamimi (State Institute of Islamic Studies (IAIN) Palu, 2006)
New Order Government is perceived by many as a unique socio-political sphere. At the time, nobody acknowledged that New Order was democratic and provided a sufficient public sphere to grow and develop a culture of different ideas. However, it was in that epoch that Islamic thought in Indonesia suffered a significant development, that was in the past a quarter century before the reformation era. How to describe the Islamic thought in Indonesia in transition era to come to democracy? This article will describe the phenomena. Kata Kunci : Pemikiran Islam, era transisi, Orde Baru